Physical activity guidelines and cardiovascular risk in children: a cross sectional analysis to determine whether 60 minutes is enough. (December 2015) - Füssenich, L.; Boddy, L.; Green, D.; Graves, L.; Foweather, L.; Dagger, R.; McWhannell, N.; Henaghan, J.; Ridgers, N.; Stratton, G.; Hopkins, N.
Abstract Background Physical activity reduces cardiovascular mortality and morbidity. The World Health Organisation (WHO) recommends children engage in 60 min daily moderate-to-vigorous physical activity (MVPA). The effect of compliance with this recommendation on childhood cardiovascular risk has not been empirically tested. To evaluate whether achieving recommendations results in reduced composite-cardiovascular risk score (CCVR) in children, and to examine if vigorous PA (VPA) has independent risk-reduction effects. Methods PA was measured using accelerometry in 182 children (9–11 years). Subjects were grouped according to achievement of 60 min daily MVPA (active) or not (inactive). CCVR was calculated (sum of z-scores: DXA body fat %, blood pressure, VO2 peak, flow mediated dilation, left ventricular diastolic function; CVR score ≥1SD indicated 'higher risk'). The cohort was further split into quintiles for VPA and odds ratios (OR) calculated for each quintile. Results Active children (92 (53 boys)) undertook more MVPA (38 ± 11 min, P  < 0.001), had greater VO2 peak (4.5 ± 0.8 ml/kg/minP  < 0.001), and lower fat % (3.9 ± 1.1 %, P  < 0.001) than inactive. No difference were observed between active and inactive for CCVR or OR (P  > 0.05). CCVR in the lowest VPA quintile was significantly greater than the highest quintile (3.9 ± 0.6, P  < 0.05), and the OR was 4.7 times higher. Conclusion Achievement of current guidelines has positive effects on body composition and cardiorespiratory fitness, but not CCVR. Vigorous physical activity appears to have beneficial effects on CVD risk, independent of moderate PA, implying a more prescriptive approach may be needed for future VPA guidelines.